2016
DOI: 10.1002/biof.1256
|View full text |Cite
|
Sign up to set email alerts
|

Phloretin‐induced cytoprotective effects on mammalian cells: A mechanistic view and future directions

Abstract: Phloretin (C15H14O5), a dihydrochalcone flavonoid, is mainly found in fruit, leaves, and roots of apple tree. Phloretin exerts antioxidant, anti‐inflammatory, and anti‐tumor activities in mammalian cells through mechanisms that have been partially elucidated throughout the years. Phloretin bioavailability is well known in humans, but still remains to be better studied in experimental animals, such as mouse and rat. The focus of the present review is to gather information regarding the mechanisms involved in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(3 citation statements)
references
References 216 publications
(232 reference statements)
0
3
0
Order By: Relevance
“…Hesperetin, a flavonoid, could suppress MAPK and TLR4/NF-κB signaling to alleviate LPS-induced neuroinflammation ( Jo et al, 2019 ; Muhammad et al, 2019 ). Phloretin is also a flavonoid with promising anti-inflammatory effects, and many models of inflammation have also been used to explore the anti-inflammatory activity and mechanism of phloretin ( de Oliveira, 2016 ). Sunil et al (2021) reported that the protective effects of (+)–catechin against RAW 264.7 cells inflammation induced by LPS via inhibiting the expression of NF-κB and p38 MAPK ( Sunil et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hesperetin, a flavonoid, could suppress MAPK and TLR4/NF-κB signaling to alleviate LPS-induced neuroinflammation ( Jo et al, 2019 ; Muhammad et al, 2019 ). Phloretin is also a flavonoid with promising anti-inflammatory effects, and many models of inflammation have also been used to explore the anti-inflammatory activity and mechanism of phloretin ( de Oliveira, 2016 ). Sunil et al (2021) reported that the protective effects of (+)–catechin against RAW 264.7 cells inflammation induced by LPS via inhibiting the expression of NF-κB and p38 MAPK ( Sunil et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…To do so, the sperm cells were resuspended in an isotonic medium, corrected to 300 mOsm, comprising 137 mM NaCl, 2.7 mM KCl, 10 mM Na 2 HPO 4 , and 1.8 mM KH 2 PO 4 , and 1 mM PMSF at a concentration of 20-30 million sperm cells per mL, and left for 10 min for stabilization. Then, sperm cells from 30 normozoospermic men were incubated for 10 min, with a specific AQP3 inhibitor (iAQP3, 200 nM of DFP00173), a specific AQP7 inhibitor (iAQP7, 200 nM of Z433927330), a general inhibitor of the mediated transport of glycerol phloretin (PHL, 0.35 mM), or the vehicle (DMSO at 1%) [17,18]. Sperm cells from 30 asthenozoospermic men (when the total motility was <40%) were also collected (Table 1), and incubated in the presence and absence of iAQP7, for comparison with the samples from normozoospermic men.…”
Section: Patient Characterization and Study Designmentioning
confidence: 99%
“…4 Phloretin is a dihydrochalcone flavonoid found in fruits, leaves, and roots of apple trees and Prunusmandshurica. 4 In animal models, phloretin has been shown to have anti-oxidant, 5 anti-inflammatory, 6,7 anticancer, [8][9][10] and immunomodulatory [11][12][13] properties. Phloretin treatment also improves glucose and lipid metabolism in streptozotocin (STZ)-induced diabetes in rats.…”
Section: Introductionmentioning
confidence: 99%